+0  
 
0
250
3
avatar

\({(6 \sqrt [3] {2} -4{\sqrt{13})}^{2} }\)

Guest Sep 24, 2017
 #1
avatar+90023 
+1

( 6∛2 - 4√13)^2  =

 

( 6∛2 - 4√13) ( 6∛2 - 4√13)  =

 

36∛4 - 24*√13*∛2 - 24*√13*∛2 + 16*13 ) =

 

36∛4 - 48*√13*∛2 + 208

 

 

 

cool cool cool

CPhill  Sep 24, 2017
 #2
avatar
0

how'd you get 208 ?

Guest Sep 25, 2017
 #3
avatar+7324 
+1

When you multiply the "last" terms, you get.....

 

-4√13 * -4√13   =   16 * √13 * √13   =   16 * √132   =   16 * 13   =   208

hectictar  Sep 25, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.